Period poverty among adolescent girls from the City of Manila, Philippines: Determinants and Impacts on their wellbeing - Tapil, Janice V. (Animo Repository, 2021)
This study determines and describes the level of period poverty of 60 adolescent girls from the City of Manila and its association with their socio-demographic, household characteristics, and physiological and psych-emotional well-being. Online survey was used to gather the data through a self-administered questionnaire via Kobo Toolbox. IBM SPSS version 26 was used to process the data using both descriptive and inferential statistics. The study revealed that almost all respondents are poor, and their parents have low educational attainment. Most have access to water and toilet at home and have a range of one to seven household members. Statistical test results showed that period poverty is evident to adolescent girls. Of the four domains, menstrual hygiene practices yielded a high score, and proper waste management has a moderate score. In contrast, information seeking and pain management practices have a low score. Further, the study showed that certain socio-demographic and household characteristics such as family monthly income, parents’ occupation, and water source could increase the likelihood of adolescent girls to experience period poverty. Meanwhile, the study revealed that adolescent girls’ well-being is at risk during menstruation. The experience of period poverty of adolescent girls, specifically their information seeking behavior, can exacerbate their emotional well-being. This study concludes that girls from an urban poor community and belong to a poor family could heighten their exposure to period poverty, which puts their well-being in poor condition. Further studies on adolescent girls coping strategies in addressing period poverty are recommended, including other determinants should be explored so that policies can be created to protect the well-being of adolescent girls.